2003
DOI: 10.1093/jxb/erg141
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Rubisco: the amount, activity, function and regulation

Abstract: Genetic modification to increase the specificity of Rubisco for CO(2) relative to O(2) and to increase the catalytic rate of Rubisco in crop plants would have great agronomic importance. The availability of three-dimensional structures of Rubisco at atomic resolution and the characterization of site-directed mutants have greatly enhanced the understanding of the catalytic mechanism of Rubisco. Considerable progress has been made in identifying natural variation in the catalytic properties of Rubisco from diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
206
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(218 citation statements)
references
References 127 publications
7
206
0
5
Order By: Relevance
“…This destabilization could directly alter the catalytic parameters by allowing more flexibility in loop 6, thus affecting the opening and closing of the active site (16). Extensive studies of this loop region in algal and cyanobacterial RubisCOs have shown that catalytic parameters are sensitive to its modification even if the mutated residues have no direct interaction with substrates (30). L270I is located directly beneath H298, which interacts with the P5 phosphate in the preactivated state.…”
Section: Analysis Of Mutations Occurring During Evolution and Their Ementioning
confidence: 99%
“…This destabilization could directly alter the catalytic parameters by allowing more flexibility in loop 6, thus affecting the opening and closing of the active site (16). Extensive studies of this loop region in algal and cyanobacterial RubisCOs have shown that catalytic parameters are sensitive to its modification even if the mutated residues have no direct interaction with substrates (30). L270I is located directly beneath H298, which interacts with the P5 phosphate in the preactivated state.…”
Section: Analysis Of Mutations Occurring During Evolution and Their Ementioning
confidence: 99%
“…Many agriculturally important crops, including cereals such as rice (Oryza sativa) and most woody perennials, are classified as C 3 plants. Their photosynthetic rate at present atmospheric CO 2 level is limited by the activity of Rubisco because of its extremely low catalytic turnover rate (k cat ) and competing oxygenase reaction, which initiates wasteful photorespiration (von Caemmerer and Quick, 2000;Parry et al, 2003). To compensate for these detrimental enzymatic properties, C 3 plants invest 15% to 35% of total leaf nitrogen in this single enzyme (Evans, 1989;Makino et al, 1992).…”
mentioning
confidence: 99%
“…In Arabidopsis, per gm fresh weight, leaves have higher amount of protein content than roots, flowers and siliques mostly due to the presence of rubisco which accounts for 50 % of total protein. (Parry et al 2003). The higher demand of huge amount of nitrogen is met by the nitrogen and sulfur assimilation pathway operating chiefly in leaves.…”
Section: Discussionmentioning
confidence: 99%